Growth–trait relationships in subtropical forest are stronger at higher diversity. (28th July 2019) - Bongers, Franca J.; Schmid, Bernhard; Sun, Zhenkai; Li, Yin; Härdtle, Werner; von Oheimb, Goddert; Li, Ying; Li, Shan; Staab, Michael; Ma, Keping; Liu, Xiaojuan
Abstract: Understanding how species diversity affects plant performance is a central question in biodiversity–ecosystem functioning (BEF) research. At the community level, functional trait means and trait dissimilarities have been used to explain biodiversity effects, but with mixed success. To disentangle how functional traits explain community growth and underpin biodiversity–ecosystem functioning relationships, we should elucidate how plant traits affect individual growth across species richness levels, because the role of functional traits on growth depends on the ecological context of the individual. We addressed this topic by using detailed data of twelve functional traits and annual growth for 529 individual trees of 31 species at five species‐richness levels in a large forest biodiversity experiment in south‐east China from 4 to 9 years after planting. Our analyses show first that individual trait values can change with species richness, indicating that trait values can change due to the biotic context. Secondly, we show that early tree growth is more strongly affected by traits than by species richness. Finally, our data show that growth–trait relationships can change with species richness and with forest age. Trait effects on growth are more pronounced at higher richness levels, indicating that measuring traits on individual trees across richness levels can improve growth predictions and inference of BEF relationships that are shaped by functional traits. Synthesis . This study shows that functional trait values and their effect on individual tree growth depend on species richness. Our data support the notion that to elucidate how functional traits shape biodiversity–ecosystem functioning relationships, an important step is to consider the biotic context of individual trees within a community. We have made an initial step by analysing how functional traits affect individual‐tree growth in a diversity‐dependent manner and future research should continue by elucidating the role of traits on tree–tree interactions across diversity levels. Abstract : Our study made an initial step to show trait effects on growth are more pronounced at higher richness levels, indicating that to elucidate how functional traits shape biodiversity–ecosystem functioning relationships, an important step is to consider the biotic context of individual trees within a community. Editor's Choice Abstract in Chinese: 物种多样性对植物在群落中性能的影响是当前生物多样性与生态系统功能（BEF）研究中的核心问题之一。尽管在群落水平上, 常用功能性状均值和相异性来解释生物多样性效应, 但至今未能得出一致结论。这主要是因为功能性状对群落动态的影响主要取决于群落中个体所处的生态环境。因此厘清功能性状对群落动态的影响及其对生物多样性‐生态系统功能关系的贡献, 应首先阐明不同物种多样性水平下植物功能性状对个体动态的影响机制。 本研究以中国东南部亚热带地区大型森林多样性与生态系统功能实验中所种植的31个物种529株乔木为研究对象, 通过对其在五个多样性水平下栽种4‐9年后生长的连续监测及测取12种植物功能性状开展了相关研究。 研究结果表明植物个体功能性状随着群落多样性的变化而变化, 说明生物环境能够影响功能性状；其次, 功能性状对树木早期生长的影响要强于物种多样性；结果还表明功能性状与生长的关系随着群落多样性和林龄的不同而变化。在物种丰富度更高的群落, 功能性状对生长的影响更明显。这说明在不同多样性水平的群落中, 测取个体水平的功能性状能够提高对生长的预测和对功能性状影响的BEF关系的推断。 综合以上, 研究结果显示植物功能性状对木本植物个体的影响取决于其所在群落的物种丰富度。因此我们认为阐明功能性状对BEF关系的影响机制, 必须要将群落中个体所处的生物环境考虑在内。这是首次关于功能性状如何依赖于多样性而影响树木个体生长的研究, 并提出未来应着重于研究不同多样性水平下功能性状在种间相互作用中的贡献。